Color-tunable upconversion luminescence and temperature sensing behavior of Tm3+/Yb3+ codoped Y2Ti2O7 phosphors. (April 2019) - Tu, Xubin; Xu, Jinsheng; Li, Mengchao; Xie, Tian; Lei, Ruoshan; Wang, Huanping; Xu, Shiqing
Graphical abstract: Schematic representation for the potential applications of Y2 Ti2 O7 :Tm 3+ /Yb 3+ phosphors. Highlights: The UC color can be tuned from almost white to blue with increasing pump power. Power-insensitive thermometry is gained based on FIR of 1 G4(a) to 1 G4(b) . The highest relative sensitivity is 0.81% K −1 based on FIR of 3 F2, 3 to 1 G4(b) . Abstract: Tm 3+ /Yb 3+ : Y2 Ti2 O7 phosphors with color-tunable upconversion (UC) luminescence and optical thermometric property were synthesized and characterized. The phosphors exhibit intense blue and red UC emission bands under 980 nm excitation. The blue to red emission intensity ratio shows an enhancement with increasing excitation power. Hence, the UC color can be tuned from almost white to blue by control of the excitation power density. The temperature sensing behaviors are studied based on fluorescence intensity ratio (FIR) technique at different excitation powers. FIR-1 from the thermally coupled levels ( 1 G4(a) and 1 G4(b) ) is insensitive to the excitation power, which can obtain consistent measurement results at different excitation powers. Meanwhile, the utilization of FIR-2 from non-thermally coupled levels ( 3 F2, 3 and 1 G4(b) ) can achieve higher sensing sensitivities with the maximal value of ∼0.81%K −1 at 398 K. Hence, Tm 3+ /Yb 3+ :Y2 Ti2 O7 phosphor has promising application prospects in the fields of upconverter, optical thermometer and color tunable device.